2011
DOI: 10.1177/1468087411405104
|View full text |Cite
|
Sign up to set email alerts
|

Model-based comparative study of Euro 6 diesel aftertreatment concepts, focusing on fuel consumption

Abstract: A model-based study is used to assess various Euro 6 diesel PM/NO x aftertreatment concepts for one specific engine and vehicle combination. The assessment focuses on fuel consumption/carbon dioxide (CO 2 ) emissions considering the fuel penalties resulting from both a periodically regenerating system as well as a catalyst heat-up strategy. The modelling work is carried out with a complete platform for simulating transient thermal and chemical phenomena of all exhaust aftertreatment components.It is shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…The maximum loading for this second test agrees with the value commonly accepted as high soot loading to promote active regeneration [25] because of excessive pressure drop and hence fuel penalty [19,26]. In fact, although the optimum soot loading to perform active regeneration reducing fuel penalty depends on the specific strategy [20], studies performed by Singh et al [27] found the optimum soot loading in 5.5 g/l to limit the fuel penalty due to excessive pressure drop. This low value strengthens the interest for pressure drop limitation at the same time that the active regeneration is delayed to high soot loading values.…”
Section: Types Of Testssupporting
confidence: 67%
See 1 more Smart Citation
“…The maximum loading for this second test agrees with the value commonly accepted as high soot loading to promote active regeneration [25] because of excessive pressure drop and hence fuel penalty [19,26]. In fact, although the optimum soot loading to perform active regeneration reducing fuel penalty depends on the specific strategy [20], studies performed by Singh et al [27] found the optimum soot loading in 5.5 g/l to limit the fuel penalty due to excessive pressure drop. This low value strengthens the interest for pressure drop limitation at the same time that the active regeneration is delayed to high soot loading values.…”
Section: Types Of Testssupporting
confidence: 67%
“…The quantification of the fuel penalty due to the regeneration process assuming it occurs throughout the cycle reported a decrease of the fuel efficiency between 31% and 52.3% with respect to a cycle without regeneration. These results and variability, which are depending on the regeneration strategy and driving cycle, are similar to the conclusions obtained by Tourlonias and Koltsakis [20], who applied a modelling approach to analyse the regeneration fuel penalty. In this work a fuel consumption increase between 16% and 21%, as a function of the regeneration strategy, was obtained during a New European Driving Cycle (NEDC) in which was taking place the DPF regeneration.…”
supporting
confidence: 74%
“…Therefore, the dosing of urea is not performed below this temperature. In this context, the pre-turbo configuration would provide higher temperature (30 − 50 o C) at the inlet of the SCR in comparison with the post-turbo configuration from the second UDC, what would contribute to reduce the heat-up strategies [31] and to increase the NO x conversion efficiency at the end of the cycle.…”
Section: New European Driving Cyclementioning
confidence: 99%
“…Usually, the DPF is placed downstream of the Diesel oxidation catalyst (DOC) to take advantage from the NO 2 generation and the increase in temperature due to DOC exothermic chemical reactions. Nevertheless, passive regeneration occurrences are not frequent during actual engine operation and the need for active regeneration strategies arises leading to fuel consumption damage [13] besides that produced by the increasing back-pressure as the DPF is loaded.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies performed by Tourlonias and Koltsakis [13] points out the suitability of selective catalytic reduction (SCR) systems placed upstream the DOC and DPF for NO x reduction. However, this configuration damages passive regeneration and delays DOC lightoff causing an additional increase in fuel consumption.…”
Section: Introductionmentioning
confidence: 99%